2015
DOI: 10.1242/jeb.122424
|View full text |Cite
|
Sign up to set email alerts
|

Vocal performance affects metabolic rate in dolphins: implications for animals communicating in noisy environments

Abstract: Many animals produce louder, longer or more repetitious vocalizations to compensate for increases in environmental noise. Biological costs of increased vocal effort in response to noise, including energetic costs, remain empirically undefined in many taxa, particularly in marine mammals that rely on sound for fundamental biological functions in increasingly noisy habitats. For this investigation, we tested the hypothesis that an increase in vocal effort would result in an energetic cost to the signaler by expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 41 publications
3
49
2
Order By: Relevance
“…This study suggests that the acoustic parameters of whistle vocalizations vary naturally according to behavioural context and group composition, but are also influenced by tour boat presence and engine noise. The vocalization changes we observed in the presence of one or more tour boats could have a long-term, negative influence on the bottlenose dolphin population in Walvis Bay if they reduce the communication range of whistles (Jensen et al, 2009), result in increased energy expenditure (Holt, Noren, Dunkin, & Williams, 2015;Williams et al, 2006) or elevate stress levels (Rolland et al, 2012;Romano et al, 2004). Such effects would be compounded if combined with other behavioural responses to tour boat presence that increase energy expenditure, for example increased socializing or travelling (Indurkhya, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study suggests that the acoustic parameters of whistle vocalizations vary naturally according to behavioural context and group composition, but are also influenced by tour boat presence and engine noise. The vocalization changes we observed in the presence of one or more tour boats could have a long-term, negative influence on the bottlenose dolphin population in Walvis Bay if they reduce the communication range of whistles (Jensen et al, 2009), result in increased energy expenditure (Holt, Noren, Dunkin, & Williams, 2015;Williams et al, 2006) or elevate stress levels (Rolland et al, 2012;Romano et al, 2004). Such effects would be compounded if combined with other behavioural responses to tour boat presence that increase energy expenditure, for example increased socializing or travelling (Indurkhya, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…As we could not measure whistle source levels, it was not possible for us to determine whether the shifts in frequency we observed were accompanied by amplitude modifications. Previous studies investigating the Lombard effect in cetaceans did not investigate concurrent changes in signal frequency (Holt et al, 2009;Scheifele et al, 2005) or failed to demonstrate a frequency shift associated with increased amplitude (Holt et al, 2015;Parks et al, 2011). However, as this research area is in its infancy, a possible coupling between the Lombard effect and other noise-induced vocal modifications in cetaceans warrants further investigation (Hotchkin & Parks, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many animals produce louder, longer, or more repetitious vocalizations to compensate for increases in environmental noise (Parks et al, 2011;Holt et al, 2015). Further, Holt et al (2015) found that an increase in vocal effort between captive common bottlenose dolphins, Tursiops truncatus, created an increase in metabolic rate and oxygen consumption over a resting period that followed sound production in both animals, and that the metabolic cost may add up over time when the individuals must compensate for chronic background noise.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Holt et al (2015) found that an increase in vocal effort between captive common bottlenose dolphins, Tursiops truncatus, created an increase in metabolic rate and oxygen consumption over a resting period that followed sound production in both animals, and that the metabolic cost may add up over time when the individuals must compensate for chronic background noise. A similar metabolic effect may be of concern for Cook Inlet belugas, particularly with an increase in ambient noise levels due to increases in shipping and construction activity.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2017) reported a theoretical 30.5% increase in beaked whale metabolic rate, with an elevated rate being maintained for more than 90 min after the exposure to noise. Even increasing the amplitude of vocalizations-so that calls may be heard in a noisy environment-may have an energetic cost (Holt et al, 2015).…”
Section: The Received Levels Of Sonar and Beaked Whales Impactsmentioning
confidence: 99%